Microwave-assisted Synthesis of Novel Triazolyl Pyrazolyl Pyrazoline Substituted Coumarins and Their Antimicrobial Activity - Kundaliya, Kaushik N.; Patel, Niraj H.; Brahmbhatt, Dinker I. (Current Microwave Chemistry, 2022)
Background: The 1,2,3-triazole, pyrazole, and coumarin-based derivatives have received much attention due to their wide coverage of biological properties. The present work describes the microwave synthesis of novel triazolyl pyrazolyl pyrazoline substituted coumarins. The structures of all the newly synthesized compounds are characterized by spectral analysis and screened for their in vitro antimicrobial activity by the Broth dilution method. Methods: Using the synthetic method, the targets were prepared by reacting various 3-3-[3-(5- methyl-1-aryl-1H-1,2,3-triazol-4-yl)-1-phenyl-1H-pyrazol-4-yl]acryloyl coumarins (coumarin chalcones) (3a-d) with hydrazine hydrate or aryl hydrazine (5a-c) in the presence of acetic/propionic acid under microwave irradiation. Results: The structures of all the synthesized compounds were established by IR, 1H-NMR, 13CAPT, and selected mass spectral data. The target compounds were also screened for their in vitro antimicrobial efficiency against a representative panel of pathogenic strains, specifically Gram-positive bacteria (Staphylococcus aureus, Bacillus subtilis), Gram-negative bacteria (Escherichia coli, Salmonella typhi), and Fungi (Candida albicans, Aspergillusniger). Conclusion: In conclusion, the target compounds were obtained by Microwave Irradiation (MWI) technique in good yield with a short reaction time. Among all the synthesized compounds, 4c, 4h, 6a, 6h, and 6l were found to have significant activity against bacterial and fungal strains.
Keywords: antimicrobial screening